(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article analyzes the need to develop ethical considerations for the use of artificial intelligence (AI) by modern human civilization in an era of rapid development and application of digital solutions in many spheres of human life. New AI technologies are being developed that are becoming a powerful force and could pose a threat to both individuals and all of humanity. This factor necessitates examining AI within the framework of ethics and morality, its basic principles and norms, and the development of a special Code of Ethics in the field of AI. This Code could establish general ethical standards and principles of behavior that should guide the activities of participants in AI-related relationships.